Rate dependent fracture along a silicon/epoxy interface under mixed-mode loading conditions. (5th December 2022) - Yang, Tianhao; Gandhi, Vatsa; Huang, Rui; Liechti, Kenneth M.
Abstract: This paper describes the development of a dual-actuator loading device that was then used to apply asymmetric, transverse end-displacements to laminated beam specimens (silicon/epoxy/silicon) over a range of separation rates. Measurements of the reaction forces, as well as load-point displacements and rotations, were used to determine the normal and tangential components of the crack tip displacements and the corresponding components of the J-integral. This was made possible because the specimens identically satisfied a balance condition. The resulting data set obtained from experiments conducted at five separation rates at each of five mode-mix phase angles is a testimony to the efficiency of the approach. A mixed-mode beam on elastic foundation analysis established that the stiffness of the normal and shear interactions of the silicon/epoxy interface was independent of the separation rate and mode-mix. Furthermore, the stiffness values thus determined were considerably lower than those based on the bulk behavior of the epoxy in tension and shear. The analysis also allowed the crack growth to be tracked in order to establish its onset and the corresponding critical values of the normal and shear components of the J-integral, along with the corresponding strengths and critical crack tip displacements. For each mode-mix, these critical values increased with the separation rate. This increase in properties is in spite of the glassy nature of the bulk epoxy and further suggests the presence of an interphase region in the epoxy adjacent to the silicon. However, the change of mode-mix was accompanied by a change in local separation rates, leading to non-monotonic behavior in the critical J-integral. Following the onset of crack growth, the application of the transverse end-displacements along radial loading paths resulted in simultaneous changes in the local separation rates and mode-mix, implying a fracture criterion that depends on both mode-mix and rate-dependent damage evolution processes.